Incidence of hypoglycemia in newborns at risk and an audit of the 2011 American academy of pediatrics guideline for hypoglycemia - Hosagasi, Nihan Hilal; Aydin, Mustafa; Zenciroglu, Aysegul; Ustun, Nuran; Beken, Serdar (Elsevier Taiwan, 2018)
Background: Hypoglycemia is low blood glucose level that may negatively affect neurological and developmental prognosis. The American Academy of Pediatrics (AAP), Committee on Fetus and Newborn defined the safe glucose concentrations in the 2011 guideline for newborns at risk for hypoglycemia. This study aimed to investigate the incidence and associated risk factors for hypoglycemia in newborn infants having risk and to assess compliance with the AAP guideline. Methods: According to 2011 AAP guideline for hypoglycemia, the newborns at risk for hypoglycemia included in this study were divided to four groups [infant of diabetic mother (IDM), large-for-gestational-age (LGA) infants, small-for-gestational-age (SGA) infants, and late preterm infants (LPI)]. Results: Of the 207 newborn infants, there were 12 cases in IDM group (5.7%), 79 cases in LGA group (38.1%), 66 cases in SGA group (31.8%) and 50 cases in LPI group (24.1%). The incidences of hypoglycemia in these four groups were 2 (16.6%), 10 (12.7%), 8 (12.2%) and 17 (34%), respectively. Although the gender, delivery method, birth weight and 5-min Apgar score at 5-min were not found to be associated with hypoglycemia (P > 0.05), lower gestational age was determined to be associated with higher incidence of hypoglycemia (P = 0.02). Median first feeding time was 55 min and time between first nutrition and blood glucose measurement was 30 min in all cases. Conclusion: Highest risk for hypoglycemia in early postnatal period was present especially in LPI group. Our compliance levels with the AAP guideline was found to be satisfactory. Copyright (C) 2017, Taiwan Pediatric Association. Published by Elsevier Taiwan LLC.
Keywords: Neonatal hypoglycemia; Incidence; Risk factors; American academy of pediatrics guideline; Breastfeeding; Blood glucose checking; Newborn